Efficacy and safety of thoracoscopic-guided multiple paravertebral block for video-assisted thoracoscopic lobectomy surgery: a randomized blinded controlled study - Li, Zhixiong; Lin, Qingshui; Lin, Liangqing; Wu, Qinghua; Ke, Pinhui; Chen, Huan; Lin, Chunlan; Yu, Yaohua (Frontiers in Surgery, 2023)
Background: Paravertebral block (PVB) has been increasingly popular for postoperative analgesia. However, few studies estimated the efficacy and safety of multiple PVB using thoracoscope-assisted technique for intraoperative analgesia and postoperative pain management for video-assisted thoracoscopic lobectomy (VATS LOBECTOMY). Methods: A total of 120 patients scheduled for VATS LOBECTOMY were randomly assigned into two groups, to either placebo group or PVB group in a 1:2 ratio. Thoracoscopic-guided multi-points PVB was carried out with 0.5% ropivacaine (PVB group) or 0.9% NaCl (placebo group) at the beginning and the end of the surgery. The primary endpoint was intraoperative opioid consumption. Results: Intraoperative opioids consumption was significantly lower in PVB group (878.14±98.37 vs. 1432.20±383.53 for remifentanil; 123.83±17.98 vs. 266.42±41.97 for fentanyl). Postoperatively, significantly longer duration of first time PCIA usage, less times of analgesic pump pressing and less rescue analgetic consumption were observed in PVB group. VAS scores at rest and during exercising were significantly lower in PVB group at all time points within the first 48h after surgery. PVB group was also associated with significantly higher total QoR-40 scores and lower incidence of analgesia related adverse events. Conclusions: Thoracoscopic-guided multiple PVB was simple and effective in controlling pain both intra- and postoperatively for VATS LOBECTOMY. It was also associated with absence of detrimental effects due to opioid overuse and benefits of the early resumption of activity and physical function recovery. Therefore, this regional anesthesia technique should be advocated as part of a multimodal analgesia protocol for VATS LOBECTOMY.